Characterization of a novel hemagglutinin of diarrhea-associated Escherichia coli that has characteristics of diffusely adhering E. coli and enteroaggregative E. coli. - Yamamoto, T (1996)
Escherichia coli 73-1 (serotype O73:H33) and 5-2 (serotype O89:H-) isolated from patients with diarrhea adhered to tissue culture cells (HeLa and HEp-2) as well as coverslips (plastic and glass) in a diffuse pattern. Adherence of strain 73-1 was mediated by a 110-kbp plasmid designated pEDA1 and correlated with D-mannose-resistant hemagglutinin (MRHA) detected with bovine, sheep, or human erythrocytes. The MRHA region was duplicated on pEDA1 and mediated the production of the 57-kDa outer membrane protein whose N-terminal amino acid sequence was hydrophobic. In accordance with MRHA and adherence, the 57-kDa outer membrane protein was observed best at 37 degrees C and to a lesser extent at 25 degrees C. In human intestine, adherence to mucus and colonic epithelium was obvious. No detectable pili were observed. The enteroaggregative E. coli heat-stable enterotoxin 1 (EAST1) gene, whose nucleotide sequence was 99.1% homologous to that of enteroaggregative E. coli, was present adjacent to the MRHA region on pEDA1. Strain 5-2 also exhibited MRHA activities and adherence and had sequences corresponding to those of the MRHA region and EAST1 gene. The data suggest that strain 73-1 (and strain 5-2), which has characteristics of both diffusely adhering E. coli and enteroaggregative E. coli, possesses a novel hemagglutinin associated with diffuse adherence.